Izhodišča za uveljavljanje informacijske pismenosti na univerzah v Sloveniji - Stopar, Karmen (Knjižnica, 2008)
Over the many years an information literate student has been one of the main goals of the universities' educational endeavours around the world. Information literacy, being the foundation of lifelong learning, is becoming increasingly important with the Bologna process. Libraries have always played a significant role in the process of more efficient and effective use of information. The Librarianship Act in Slovenia stipulates that libraries support and carry out educational and information literacy tasks. In accordance with their capabilities and the level of development of the information environment, the libraries have performed library-pedagogical tasks and have trained their users for efficient and effective use of information. Nevertheless, there is a greater need for more intensive and more comprehensive information literacy activities. The requirements of the education process through all the years of the university education should lead to better information literacy among students. All subjects, institutions and individuals, who are responsible for the realization of information literacy programmes, should join in order to implement the information literacy programmes.
Keywords: informacijska pismenost; izobraževanje; education; standardi; informacije; student; študenti; knjižnice; knjižničarji; visoko šolstvo; Slovenia; Slovenija